Antimicrobial activity of Gymnema sylvestre (Asclepiadaceae) - Beverly C. David (Journal of Acute Disease, 2013)
Objective: To evaluate antimicrobial activities of aqueous, methanol, chloroform and hexane extract of leaves plant of Gymnema sylvestre (G. sylvestre). Methods: The antimicrobial screening of the extracts of G. sylvestre against most prevalent microbes like Staphylococcus aureus (S. aureus), Bacillus cereus (B. cereus), Klebsiella pneumoniae (K. pneumoniae), Escherichia coli (E. coli), Candida albicans (C. albicans), Candida tropicalis (C. tropicalis), Candida krusei (C. krusei) and Candida kefyr (C. kefyr) by agar well diffusion method, minimum inhibitory concentration, minimum bactericidal concentration, minimum fungicidal concentration were carried out. Results: The aqueous and methanol leaf extract showed significant antibacterial and antifungal activities against the selected microorganisms when compared to the standard drugs respectively. Conclusions: The dried scale leaves of G. sylvestre might represent a new antimicrobial source with stable, biologically active components that can establish a scientific base for the use in modern medicine.